Perceptions of artificial intelligence among psychology students: Percepciones de la inteligencia artificial entre estudiantes de psicología - Nakano, Tatiana de Cassia; Sarôa Brandine, João Vitor; Vilvert, Paloma do Nascimento; Penteado Garcia, Anna Luisa; Vieira de Andrade, Maria Eduarda (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2025)
Artificial intelligence (AI) has been applied to a variety of fields of knowledge. In order to investigate students' perceptions regarding the use of artificial intelligence and possible impacts, 113 students from the first through tenth semesters of the course responded to an online questionnaire. Participants came from five Brazilian states and were aged 18 to 42 years old (M = 22.0; SD = 4.6), with 75.2% being female. The majority of respondents (92.0%) stated that they had already used AI tools, especially ChatGPT. The majority of respondents (54.8%) believed that AI could benefit psychology professionals, while 39.8% were uncertain. Most of the sample responded that they have doubts (45.1%) about the benefits of AI for the users of psychology services, and 36.2% agreed. Among the main concerns about the use of AI in Psychology are issues related to self-diagnosis, the replacement of professionals by artificial intelligence, a devaluation of the service, a reduction in student study, dissemination of superficial information, and ethical concerns. However, despite their recent introduction, AI tools have been widely implemented by psychology students, although doubts remain regarding their practical benefits, both for professionals and users.